Mitochondrial Transfer of Wharton's Jelly Mesenchymal Stem Cells Eliminates Mutation Burden and Rescues Mitochondrial Bioenergetics in Rotenone-Stressed MELAS Fibroblasts. (22nd May 2019) - Lin, Tsu-Kung; Chen, Shang-Der; Chuang, Yao-Chung; Lan, Min-Yu; Chuang, Jiin-Haur; Wang, Pei-Wen; Hsu, Te-Yao; Wang, Feng-Sheng; Tsai, Meng-Han; Huang, Sheng-Teng; Wang, Xiao-Wen; Tsai, Po-Chin; et al.
Abstract : Wharton's jelly mesenchymal stem cells (WJMSCs) transfer healthy mitochondria to cells harboring a mitochondrial DNA (mtDNA) defect. Mitochondrial myopathy, encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) is one of the major subgroups of mitochondrial diseases, caused by the mt.3243A>G point mutation in the mitochondrial tRNALeu (UUR) gene. The specific aim of the study is to investigate whether WJMSCs exert therapeutic effect for mitochondrial dysfunction in cells of MELAS patient through donating healthy mitochondria. We herein demonstrate that WJMSCs transfer healthy mitochondria into rotenone-stressed fibroblasts of a MELAS patient, thereby eliminating mutation burden and rescuing mitochondrial functions. In the coculture system in vitro study, WJMSCs transferred healthy mitochondria to rotenone-stressed MELAS fibroblasts. By inhibiting actin polymerization to block tunneling nanotubes (TNTs), the WJMSC-conducted mitochondrial transfer was abrogated. After mitochondrial transfer, the mt.3243A>G mutation burden of MELAS fibroblasts was reduced to an undetectable level, with long-term retention. Sequencing results confirmed that the transferred mitochondria were donated from WJMSCs. Furthermore, mitochondrial transfer of WJMSCs to MELAS fibroblasts improves mitochondrial functions and cellular performance, including protein translation of respiratory complexes, ROS overexpression, mitochondrial membrane potential, mitochondrial morphology and bioenergetics, cell proliferation, mitochondrion-dependent viability, and apoptotic resistance. This study demonstrates that WJMSCs exert bioenergetic therapeutic effects through mitochondrial transfer. This finding paves the way for the development of innovative treatments for MELAS and other mitochondrial diseases.